Evaluation of plasma nucleosome concentrations and the effect of pre-analytical variables in healthy cats - Emily Westerback; Heather Wilson-Robles; M’hammed Bougoussa; Stephanie Istvan; Samuel Stewart; Emma Warry; Justin Heinz (BMC Veterinary Research)
Abstract Background Nucleosome levels have been shown to increase in dogs and humans in certain disease states, as a result of cell apoptosis, raising interest in their utility as a biomarker. Detection of nucleosomes in feline blood has yet to be described. Optimal collection tube and processing technique for samples intended for nucleosome analysis varies in the available veterinary and human literature. The aims of this study were to evaluate nucleosome concentration in blood obtained from healthy cats, and describe the impact of collection and processing methods, including tube type, centrifugation protocol, and time to sample processing. Methods Blood from sixty-four client-owned healthy domestic cats was collected and analyzed. Samples were collected into EDTA, serum separator and sodium citrate tubes. Processing of samples was performed at different timepoints (15, 30, 60, 120 min) and under different centrifugation protocols to ascertain the most reliable sample collection and processing technique. An ELISA with a detection antibody directed at histone 3.1 was utilized to determine nucleosome concentration. Results The smaller range of nucleosome concentrations in EDTA samples indicates higher reliability of samples collected into EDTA tubes. Concentrations in samples collected into serum separator and sodium citrate tubes were widely variable in comparison to EDTA tubes. There was no significant difference when comparing H3.1 nucleosome levels from samples collected into serum separator or sodium citrate tubes at the different time points from sample collection to processing. The H3.1 nucleosome levels in the EDTA sample processed at 120-min were significantly higher than those from all other EDTA timepoints. No significant difference in nucleosome concentration was found between centrifugation protocols. Conclusions and relevance Nucleosomes can be successfully measured in blood obtained from healthy cats. EDTA tubes provided more consistent results compared to sodium citrate and serum separator tubes for evaluation of H3.1 nucleosome levels. The significant increase in nucleosome concentration in EDTA samples that were processed after 120 min justifies sample processing within one hour of collection. Samples can be processed utilizing any of the centrifugation protocols used in this study.